Analysis of Competitiveness and Forecasting of Indonesian Tea Exports to Main Destination Countries - Fadhlan Zuhdi; Khoiru Rizqy Rambe; Lola Rahmadona (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2022)
Indonesia as a tea exporter in the world has not maximized tea export opportunities as indicated by the decline in the value of tea exports from 2016 to 2020. This study aims to further analyze the competitiveness of Indonesian tea exports to major importing countries and predict the value of exports that will occur until 2025. This study used time series data from 2001-2020 which was analyzed with Revealed Comparative Advantage (RCA) and Autoregressive Integrated Moving Average (ARIMA). The results of the analysis show that the competitiveness of Indonesian tea exports to the main destination countries, namely Russia, Malaysia, China, Taiwan, and the United States, does not have a comparative advantage (RCA<1). However, based on forecasting results, the value of tea exports to Russia, Malaysia, and China is expected to increase until 2025. This increase in tea export value also has an impact in the form of strengthening the competitiveness of Indonesian tea exports in these countries even though the RCA index value is smaller than one. Thus, although the competitiveness of Indonesian tea exports is still weak in destination countries, Indonesia can optimize tea exports to countries that have increased competitiveness, such as Russia, Malaysia, and China.